The Dynamics of the Codification of Indonesian Post-Publication Republic of Indonesia Government Regulation Number 57 Year 2014 - Sudaryanto Sudaryanto; Pratomo Widodo (LPPM State University of Jakarta (Program Studi Pendidikan Bahasa dan Sastra Indonesia dan LPPM Universitas Negeri Jakarta), 2020)
The issuance of Government Regulation of the Republic of Indonesia (PP) Number 57 of 2014 concerning Development, Development and Protection of Language and Literature, as well as Improvement of the Function of Indonesian Language has made the dynamics of the Indonesian codification even more current. Before the regulation was published, the Indonesian language codification conducted by the government was limited to publishing the Big Indonesian Dictionary IV (KBBI) IV, General Guidelines for the Formation of Terms (PUPI), and General Guidelines for Improved Indonesian Spelling (PUEYD). The research method used is descriptive qualitative method. The data collection methods and techniques used include the listening method, with the basic tapping techniques and the advanced, competent free listening (SBLC) techniques. Meanwhile, the data analysis methods and techniques used include the orthographic equivalent method, with the basic technique of determining the deciding element (PUP) and the advanced comparative relationship technique equalizing the subject matter (HBSP). The results showed that the codification of Indonesian language after the issuance of PP Number 57 Year 2014 included updating the KBBI, PUPI Workshops, and publishing a number of bilingual dictionaries (Indonesian-regional languages).